"I Had Faith": Migrant Women's Use of Religion and Spirituality to Reframe Their Divorce and for Self- Reinvention. Issue 4 (19th May 2022) - Ridgway, Alexandra
ABSTRACT: Migrant women may find themselves highly isolated and marginalized if their marriage ends overseas. For divorcees who are religious or spiritual, drawing upon these belief systems can help them grieve the partnership loss while also planning for their post-divorce future. This article qualitatively examines the biographies of nine migrant women in Melbourne, Australia who constructively used their beliefs during and after divorce to reframe the precarity of their circumstances into ones of possibility. It finds that positive interactions with different forms of faith can be a valuable tool for female migrant divorcees to transcend their difficulties and begin life anew.